Comparison of the Effectiveness of Shame-Awareness Therapy and Cognitive-Behavioral Therapy on Self-Regulation Behaviors and Psychological Symptoms in Adolescent Girls with Gender Dysphoria - Shahbeyki, Maryam; Nasri, Maryam; Jafar Tabatabaei, Samaneh Sadat (Journal of Assessment and Research in Applied Counseling (JARAC), 2025)
Objective: The present study aimed to compare the effectiveness of shame-awareness therapy and cognitive-behavioral therapy (CBT) on self-regulation behaviors and psychological symptoms in adolescent girls with gender dysphoria.Methods and Materials: This research is a quasi-experimental study with a pre-test and post-test design and two intervention groups. The statistical population of the study included all girls who sought treatment in various healthcare centers in Zahedan, expressing concerns about gender identity. Using the Lovibond and Lovibond (1995) Stress, Anxiety, and Depression Scale, and the Brown, Miller, and Lawendowski (1995) Self-Regulation Questionnaire, 36 girls were selected through purposive sampling and randomly assigned to three groups. The experimental groups underwent a 13-session, 60-minute training program based on either shame-awareness therapy or CBT, while the control group received no such training. After the intervention period, a post-test was administered to all groups. Data were analyzed using multivariate analysis of covariance (MANCOVA) with SPSS statistical software.Findings: The results showed that both shame-awareness therapy and CBT had a significant effect on self-regulation behaviors and psychological symptoms in adolescent girls with gender dysphoria.Conclusion: It can be concluded that cognitive flexibility and core beliefs play a crucial role in improving body management and mental health in female students. Strengthening these factors can reduce concerns related to body image, increase body satisfaction in this group, and prevent unhealthy behaviors.